2008
DOI: 10.1063/1.3000638
|View full text |Cite
|
Sign up to set email alerts
|

Translational diffusion of water and its dependence on temperature in charged and uncharged clays: A neutron scattering study

Abstract: Structural changes of poly( N -isopropylacrylamide)-based microgels induced by hydrostatic pressure and temperature studied by small angle neutron scattering J. Chem. Phys. 133, 034901 (2010) The water diffusion in four different, highly compacted clays ͓montmorillonite in the Na-and Ca-forms, illite in the Na-and Ca-forms, kaolinite, and pyrophyllite ͑bulk dry density b = 1.85Ϯ 0.05 g / cm 3 ͔͒ was studied at the atomic level by means of quasielastic neutron scattering. The experiments were performed on two t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 50 publications
7
38
0
Order By: Relevance
“…The Gaussian distribution describes the continuous diffusion reflected in elastic scattering signals, whereas the Lorentzian distribution explains the complex diffusion process with a diffusion time greater than the neutron experimental time scale. [ 24 ] The width of the Lorentzian distribution for deuterium is broader than that of hydrogen at 77 K, indicating that the diffusion of deuterium is faster than that of hydrogen in MIL‐53(Al), which is in line with the results obtained for other rigid quantum sieving materials. [ 17 ]…”
Section: Figuresupporting
confidence: 81%
“…The Gaussian distribution describes the continuous diffusion reflected in elastic scattering signals, whereas the Lorentzian distribution explains the complex diffusion process with a diffusion time greater than the neutron experimental time scale. [ 24 ] The width of the Lorentzian distribution for deuterium is broader than that of hydrogen at 77 K, indicating that the diffusion of deuterium is faster than that of hydrogen in MIL‐53(Al), which is in line with the results obtained for other rigid quantum sieving materials. [ 17 ]…”
Section: Figuresupporting
confidence: 81%
“…However, such a relationship remains to be investigated in the case of clay media made of swelling clay particles with two types of porosities (i.e., interlayer and interparticle) being accessible for the water. In such dual-porosity media with charged surfaces, water mobility in the interlayer space can be drastically reduced compared to that in the interparticle porosity, as revealed by molecular dynamic simulations (Titiloye and Skipper, 2001;Marry et al, 2002;Malikova et al, 2006;Michot et al, 2012 among others) and quasi-elastic neutron scattering studies (González Sánchez et al, 2008a;Bestel, 2014) performed on low charge swelling clays, e.g. montmorillonite.…”
Section: Introductionmentioning
confidence: 99%
“…18 Other studies into diffusion of water, the dependence on temperature, and hydration in clay systems were carried out through experiments and simulations. [19][20][21][22][23][24][25] Desai et al found that the included water is likely to cause the phases in the bentonite clays. 26 Thus our present study of the hydration of Laponite and its phase behavior is studied systematically with aging.…”
Section: Introductionmentioning
confidence: 99%